Durvalumab‐induced lesions of bronchiolitis and fully reversible bronchiectasis in a patient with non‐small cell lung cancer: A case report. Issue 8 (23rd February 2021) - Domblides, Maël; Geier, Margaux; Decroisette, Chantal; Descourt, Renaud
Abstract: Durvalumab is a humanized monoclonal antibody targeting programmed cell death ligand‐1 (PD‐L1), leading to an antitumor activity, used as consolidation therapy in patients with locally advanced unresectable non‐small cell lung cancer (NSCLC). Several immune‐related adverse events (irAEs) have previously been described in patients following treatment with immune checkpoint inhibitors (ICIs). To the best of our knowledge, we report the first case of immunotherapy‐induced fully reversible bronchiolitis and bronchiectasis, despite the fact that its pathophysiological mechanism has been previously considered to be irreversible. Abstract : Here we report a case of durvalumab‐induced lesions of bronchiolitis and fully reversible bronchiectasis. This immune‐related adverse event has not previously been described.